Novel pathway of 3-hydroxyanthranilic acid formation in limazepine biosynthesis reveals evolutionary relation between phenazines and pyrrolobenzodiazepines - Pavlikova, Magdalena; Kamenik, Zdenek; Janata, Jiri; Kadlcik, Stanislav; Kuzma, Marek; Najmanova, Lucie (Scientific reports, 2018)
Natural pyrrolobenzodiazepines (PBDs) form a large and structurally diverse group of antitumour microbial metabolites produced through complex pathways, which are encoded within biosynthetic gene clusters. We sequenced the gene cluster of limazepines and proposed their biosynthetic pathway based on comparison with five available gene clusters for the biosynthesis of other PBDs. Furthermore, we tested two recombinant proteins from limazepine biosynthesis, Lim5 and Lim6, with the expected substrates in vitro. The reactions monitored by LC-MS revealed that limazepine biosynthesis involves a new way of 3-hydroxyanthranilic acid formation, which we refer to as the chorismate/DHHA pathway and which represents an alternative to the kynurenine pathway employed for the formation of the same precursor in the biosynthesis of other PBDs. The chorismate/DHHA pathway is presumably also involved in the biosynthesis of PBD tilivalline, several natural products unrelated to PBDs, and its part is shared also with phenazine biosynthesis. The similarities between limazepine and phenazine biosynthesis indicate tight evolutionary links between these groups of compounds.
Keywords: benzodiazepiny; molekulární evoluce; kyselina 3-hydroxyanthranilová; Metabolic Networks and Pathways; Sequence Analysis, Protein; Mass Spectrometry; metabolické sítě a dráhy; Chromatography, Liquid; sekvenční analýza proteinů; Streptomyces; hmotnostní spektrometrie; chromatografie kapalinová; Benzodiazepines; 3-Hydroxyanthranilic Acid; Evolution, Molecular